Technology of culinary (frying) fats - Udovenko, Oleksiy; Gladkiy, Fedir; Shkredov, Ivan; Havriushenko, Kateryna; Litvinenko, Olena; Kunitsia, Katerina (Scientific Route, Estonia, 2020)
The increased popularity of deep-fried foods has put health and safety concerns on the agenda. Factors that affect the quality and safety of culinary (frying) fats include the fatty acid profile, as well as cooking modes and time, especially when renewal rates are low. The industry is currently facing a top-of-mind technology challenge: to reduce the “oil content” of fried foods by developing a frying fat that would meet up-to-date food production standards. In other words, there is a need for a frying fat, which should last as long as possible without oxidizing and changing colour. Furthermore, its uptake by foods, fried in it, must be 40–50 % less than that of conventional fats. To this end, the authors put forward an innovative technology for producing culinary (frying) fats through esterification of fatty acids with high molecular weight alcohols. The research work that has been carried out so far prove the possibility of producing specialty fats by such modification to the applicable regulatory requirements: the melting range is between 29.6 and 34.65 °С, the acid value is up to 0.4 mg KОН/g. The viscosity of modified fats is lower than that of oils, which is due to the fat structure, and this circumstance will have a positive effect on the fat content in a finished product. The researchers has identified a numerical relationship (expressed as a regression model) of the yield of the desired fraction of a modified fat versus the ratio of reagents, reaction time, and process temperature, as well as calculated rational process parameters. The aim of the research is to develop the technology of obtaining culinary (frying) fats by esterification of fatty acids with high molecular weight alcohols.
Keywords: frying fat; esterification; acid value; oxidation; melting point; modified fat